Penyuluhan Anti Bullying Kawasan Bebas Perundungan: Pengabdian - Ratnawati, Ratnawati; Inggrayani, Lian; Zainab, Nur; Lumeno, Nanda Christherin; Qibtiyah, Mariyatul; Reni, Metri; Amelia, Winda; Abidin, Zainal (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
Bullying prevention counseling is an important preventive effort aimed at increasing students’ understanding of peer violence that commonly occurs in school environments. This study aims to determine the effectiveness of counseling in improving students’ knowledge regarding the definition, forms, impacts, and prevention of bullying. The activity was carried out by the KKN (Community Service Program) students of Batch LVI Posko 102, Universitas Alkhairat, at SD Alkhairat Pusat Palu, involving 33 fifth-grade students as participants. The method included a pre-test, educational video screening, material presentation, interactive discussion, and post-test. The findings indicate a significant improvement in students’ knowledge, with the number of students categorized as having good understanding increasing from 12 to 25 after the counseling session. This result demonstrates that interactive and communicative counseling methods positively impact students’ comprehension of bullying. Furthermore, the activity encouraged students to be more confident in reporting acts of bullying and helped strengthen respectful behaviors among peers. Therefore, continuous bullying-prevention education is essential as a strategic effort to create a safe, supportive, and violence-free school environment.